Gene Expression Divergence Between Zebra Finch (Taeniopygia Guttata) Subspecies And Gene Regulation In Hybrids - Davidson, John H. (East Carolina University, 2015)
Since the publication of Mayr's Systematics and the Origin of Species, birds have been important model organisms for studies regarding evolutionary processes such as sexual selection and speciation. In this study, I will examine patterns of expression divergence in two subspecies of the zebra finch Taeniopygia guttata. These two zebra finch populations have been allopatrically isolated for about one million years, thus allowing for divergence in aspects of morphology, genetics and behavior. Based on previous research, we have a detailed portrait of the timing and demographic components of divergence in these birds. However, little is known about how gene expression may contribute to genomic divergence. Among sexually reproducing organisms, the conclusion of the speciation process is thought to be evidenced by the buildup of genomic incompatibilities. The two zebra finch subspecies can mate and generate viable hybrids, allowing the use of expression data from hybrids to test for such genomic incompatibilities. Here, I will use RNA sequencing technology to quantify genome-scale patterns of expression divergence, highlighting patterns of functional divergence in the zebra finch genome.
Keywords: Evolution and development; Dobzhansky-Muller model; Incompatibility; Misregulation; Speciation; Gene expression; Genetic regulation; Species; Zebra finches